Students' Perceptions of the Online Learning System in Sociology Subjects for Class X SMA Negeri 5 Baguala District, Ambon City - Winda Souissa; H. Abarua; L. M. Sahetapy (International Journal of Education, Information Technology, and Others, 2021)
The purpose of this study was to determine how students perceive the learning system in the network/online in the subject of sociology. The type of research used is descriptive quantitative approach with percentage analysis in which the measuring instrument used is a questionnaire. The results of this study show indicators of perspective, facilities, acceptance, attitudes and understanding which can be shown in student responses with answers strongly agree as much as 14.48%, agree as much as 34.72%, doubt as much as 14.48%, disagree as much as 14.48% and disagree as much as 20.48%. Which means that students' perceptions of the online/network learning system in this sociology subject show that in doing learning students can still accept the material given even though there are few obstacles on the network